BENTUK DAN FUNGSI MUSIK DOL PADA MASYARAKAT KOTA BENGKULU - Kurniawan, Irfan; Haque, Zelly Marissa (Jurnal Seni, Desain dan Budaya)
AbstractThis article discusses the form and function of Dol music in Bengkulu city society. This study uses qualitative methods, data collection is done by observation, interviews, and documentation. The results of this study indicate that Dol music is an important element integrated in the Tabot ritual procession in the city of Bengkulu. 3 Dol music reporters in carrying out Tabot rituals, namely tamatam, swena, and sweri. The role of Dol music in the procession is to express the musical spirit of ritua tabot namely struggle, war and sadness. The existence of Dol music performance both in the context of Tabot rituals, as well as its development outside the Tabot event contest, has important values and functions for the community namely; 1) Functioning as entertainment for the community, 2) The function of emotional disclosure, seen from the emotional overflow of players in the ?beruji Dol? 3) functions as a ratification of social institutions, in this case Dol music is an important requirement in the Tabot ceremony, 4) symbolic function, as a symbol manifested through musical aspects expressing sadness or the spirit of warfare, 5) the function of community integration, uniting the community in togetherness and being involved in the wisdom of the Tabot ceremony, and 6) the function of cultural continuity; the existence of Dol music as a form of effort to preserve and strengthen the cultural identity of the people of Bengkulu city.Keywords : Dol music, Tabot Rital, Form, FunctionAbstractArtikel ini membahas tentang bentuk dan fungsi musik Dol dalam kehidupan masyarakat kota Bengkulu. Penelitian ini menggunakan metode kualitatif, pengumpulan data dilakukan dengan teknik observasi, wawancara, dan dokumentasi. Permasalahan dibahas melalui deskriptif analisis. Hasil penelitian ini menunjukan bahwa musik Dol merupakan unsur penting yang terintegrasi dalam prosesi upacara Tabot di kota Bengkulu. Terdapat 3 reportoar musik Dol dalam pelaksanaan upacara Tabot yakni tamatam, swena, dan sweri. Adapun  peran musik Dol pada prosesi tersebut adalah mengekspresikan secara musikal spirit dari upacara yakni perjuangan, perperangan dan kesedihan. Keberadaan seni pertunjukan musik Dol baik dalam konteks ritual Tabot, maupun perkembangnganya diluar kontes uapacara Tabot, memiliki nilai dan fungsi penting bagi masyarakatnya yakni; 1) Berfungsi Sebagai hiburan bagi masyarakat, 2)Fungsi pengungkapan emosional, terlihat dari peluapan emosional pemain pada prosesi ?beruji Dol? 3) berfungsi sebagai pengesah lembaga sosial, dalam hal ini musik Dol merupakan syarat penting dalam upacara Tabot, 4) fungsi perlambangan, sebagai simbol yang diwujudkan melalui aspek musikal yang mengekspresikan kesedihan ataupun spirit perperangan, 5) fungsi pengintegrasian masyarakat, menyatukan masyarakat dalam kebersamaan dan terlibat dalam hikmatnya upacara Tabot, dan 6) fungsi kesenambungan budaya; eksistensi musik Dol sebagai bentuk usaha pelestarian dan penguatan idenitas budaya masyarakat kota Bengkulu.Kata kunci : Musik Dol, upacara Tabot, Bentuk, Fungsi